Guilty of doing …... nothing: should there be criminal liability for failure to rescue strangers in England and Wales? - Siddiqui, Usmaan (2019)
It is late at night and James has collapsed on the side of the road. James requires urgent attention. Harry comes across James and sees his plight, in agony, pleading for help. However, Harry is in a hurry to get home and walks on by. James dies a few minutes later.